Tracking of u-turn behaviour for heavy vehicles at three locations along FR2 (Gambang to Kuantan) - Mohamad Azmil Sahidan, Abdul Shatar (2019)
The present study provides a methodology for identification of the conflict zone between a turning vehicle and on-coming vehicles at u-turn area. The main purpose of this study is to analysis the u-turn behaviour for the heavy vehicle. In the previous studies, it has been shown that the u-turn behaviour is a complex problem that requires a full understanding of drivers’ attitudes and beliefs. The understanding is needed to ensuring the safety of the other road users. Therefore, this study will analyse the u-turn behaviour of heavy vehicle based on the turning radius as a key variable in this study which may affect the result. The scenarios and road environment were based on three selected site locations along FR2 (Gambang to Kuantan).